Theoretical Modelling, Experimental Testing and Simulation Analysis of Thermal Properties for Green Building-Insulation Materials - Balo, Figen (Mdpi, 2025)
In this study, 45 alternative green materials for building walls were experimentally produced, utilizing renewable (epoxidized sesame oil), natural (clay), and waste (Seyit & ouml;mer fly ash) resources. These materials were evaluated based on key technical properties such as mass, tensile-compressive strength, and thermal conductivity, all of which are essential for construction and insulation applications. Subsequently, theoretical modeling was conducted for the material coded SE45, which demonstrated the lowest thermal conductivity. Through mathematical calculations, the theoretical thermal conductivity value was determined with a deviation of +5.88%. Furthermore, 48 alternative scenarios were designed for three different building envelope types (internally insulated, externally insulated, and sandwich), using commonly used building insulation materials alongside the sesame oil-based green material with the lowest thermal conductivity (SE45). Energy performance evaluations were conducted by analyzing temperature distributions along the walls of all designed scenarios using ANSYS simulations under the climatic conditions of Ankara, Turkey.
Keywords: epoxidized sesame oil; green building; renewable materials; ANSYS software; energy efficiency